2023
DOI: 10.1111/cdoe.12890
|View full text |Cite
|
Sign up to set email alerts
|

Labels and descriptions of dental behaviour support techniques: A scoping review of clinical practice guidelines

Caoimhin Mac Giolla Phadraig,
Pedro Vitali Kammer,
Koula Asimakopoulou
et al.

Abstract: IntroductionThere is no agreed taxonomy of the techniques used to support patients to receive professional oral healthcare. This lack of specification leads to imprecision in describing, understanding, teaching and implementing behaviour support techniques in dentistry (DBS).MethodsThis review aims to identify the labels and associated descriptors used by practitioners to describe DBS techniques, as a first step in developing a shared terminology for DBS techniques. Following registration of a protocol, a scop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…This suggests that the list possesses an acceptable initial coverage of DBS techniques and suggests further refinements to this list. Using the BeSiDe list, 10 the findings clearly demonstrate diversity in outcome measurement across types of intervention.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…This suggests that the list possesses an acceptable initial coverage of DBS techniques and suggests further refinements to this list. Using the BeSiDe list, 10 the findings clearly demonstrate diversity in outcome measurement across types of intervention.…”
Section: Discussionmentioning
confidence: 92%
“…Specific examples of this broad field include music, systematic desensitization, clinical holding, and general anesthesia. 9,10 When dental teams and patients choose which DBS to use, this involves an explicit or implicit comparison between DBS techniques and their outcomes to select the best option with the patient, considering the best evidence available. As these decisions must be evidence-based, there is a need for data on the effectiveness and safety of specific DBS techniques.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This modified e‐Delphi study followed a pre‐registered protocol, 14 with one major deviation: the categorization and sorting reported here, were originally protocoled as a separate, standalone study. In the end, both strands unfurled together.…”
Section: Methodsmentioning
confidence: 99%
“…The first step in this process, a review of DBS labels and descriptions was recently published. 11 This modified e-Delphi study, as reported here, is the second step in the process. Specifically, this study aimed to develop consensus in the labels and descriptors used for DBS techniques, and, sort these techniques theoretically, according to their underlying principles of behaviour and learning.…”
mentioning
confidence: 99%